2017
DOI: 10.1002/anie.201705685
|View full text |Cite
|
Sign up to set email alerts
|

Repairing Nanoparticle Surface Defects

Abstract: Solar devices based on semiconductor nanoparticles require the use of conductive ligands; however, replacing the native, insulating ligands with conductive metal chalcogenide complexes introduces structural defects within the crystalline nanostructure that act as traps for charge carriers. We utilized atomically thin semiconductor nanoplatelets as a convenient platform for studying, both microscopically and spectroscopically, the development of defects during ligand exchange with the conductive ligands Na4SnS4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 26 publications
(22 reference statements)
2
28
0
1
Order By: Relevance
“…Furthermore, studies utilizing charged X-type ligands to transfer QDs from nonpolar to polar media do not result in increases of PL QY. 23 28 One study by Page et al 8 claimed near-unity PL QYs in CdTe QDs as a result of X-type passivation of Cd sites by Cl – anions from added CdCl 2 , but we note that their results can be explained via Z-type passivation of Te sites by CdCl 2 . 29 , 30 L-type amine ligands pose a more significant counter-argument against the hypothesis that only a two-coordinated anion results in trap states, as they are commonly observed to increase the PL QY of CdSe QDs.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Furthermore, studies utilizing charged X-type ligands to transfer QDs from nonpolar to polar media do not result in increases of PL QY. 23 28 One study by Page et al 8 claimed near-unity PL QYs in CdTe QDs as a result of X-type passivation of Cd sites by Cl – anions from added CdCl 2 , but we note that their results can be explained via Z-type passivation of Te sites by CdCl 2 . 29 , 30 L-type amine ligands pose a more significant counter-argument against the hypothesis that only a two-coordinated anion results in trap states, as they are commonly observed to increase the PL QY of CdSe QDs.…”
Section: Introductionmentioning
confidence: 52%
“… 20 However, our results show that if Cd traps exist, they must contribute less to nonradiative recombination than Te traps and are removed by the addition of MX n ligands. (ii) Some surface reconstruction follows binding of Cl or other ligands, 28 resulting in a reduction of two-coordinated Te sites. We observed no sign of morphology changes in our treatment experiments, but this does not rule out reconstruction of the QD surface.…”
Section: Resultsmentioning
confidence: 99%
“…The increase of Φ( t )∑μ with increasing fluence is not typically observed in films of Pb- or Cd-chalcogenide QDs, although it has been observed by Savenije et al 40 for TiO 2 nanoparticles and has been attributed to filling of deep traps. Related, Marino et al 41 have shown that for CdSe nanoplatelets the PL, surface defects (deep traps), and TRMC mobility are correlated. Such deep traps quickly capture charge carriers within the 3 ns time resolution of the TRMC experiment and hence lower the maximum Φ( t )∑μ value that is measured.…”
Section: Results and Discussionmentioning
confidence: 95%
“…In addition to the transition metal oxides and transition metal salts, various layered 2D materials also show great attractiveness. For example, the metal chalcogenides, such as SnS 2 , WS 2 , CoS 2 , WS 2 , [121] and 2D-MOFs, like Mn-, Ni-, Co-2D MOF nanosheets [122] have been applied in LIBs and/or KIBs. Especially, MXenes, a large family of 2D transition metal carbides and carbonitrides, discovered by Gogotsis group, [123] have gained widespread interest as emerging potential host anode materials for DIBs, due to their unique structure, high theoretical capacity (447.8, 351.8, 191.8 mAh g À1 for LIB, NIB, and KIB on Ti 3 C 2 , respectively), [124] and adjustable interlayer space capable of accommodating cations with large ionic radius, such as Na + and K + .…”
Section: D Layered Materialsmentioning
confidence: 99%